PENGARUH PEMBELAJARAN BERBASIS MASALAH DAN KECERDASAN NATURALIS TERHADAP KEMAMPUAN SISWA DALAM MEMECAHKAN MASALAH LINGKUNGAN HIDUP (Studi Eksperimen Di SMPN 1 Mataram NTB) - Suhirman, Suhirman (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2017)
The objective of the research is to determine the influence of problem based learning, naturalistic intelligence, and their interaction on students’ ability in environment problem solving. The research was conducted at State Junior High School 1 Mataram, Nusa Tenggara Barat, 2011 with n=36 selected randomly. The research are as follows: (1) the ability in environment problem solving of the students who learned using monolithic natural environment study is significant higher than those who learned using integrated natural environment study (2) The ability in environment problem solving of those whose high naturalistic intelligence is significant higher than those whose low naturalistic intelligence (3) the ability in environment problem solving for those whose high naturalistic intelligence but learned using monolithic natural environment study is significantly higher than those who learned using the integrated one (4) the ability in environment problem solving for those whose low naturalistic intelligence but learned using monolithic natural environment study is not significant different from those who learned using the integrated one (5) the ability in environment problem solving of those who learned using monolithic natural environment study but whose high naturalistic intelligence is significant higher than those whose low naturalistic intelligence (6) the ability in environment problem solving of those whose low naturalistic intelligence but learned using monolithic natural environment study is not significant different from those who learned using the integrated one. Based on the result of research, the students’ ability in solving environmental problems might be significantly improved by teaching them using monolithic approach as well as considering their naturalistic intelligence.